Comparison of the performance and safety of 2 ophthalmic viscosurgical devices in cataract surgery - Auffarth, Gerd U.; Auerbach, Florian Niklas; Rabsilber, Tanja Marina; Holzer, Mike P. (Journal of cataract and refractive surgery, 2017)
PURPOSE: To compare the clinical performance and safety of 2 ophthalmic viscosurgical devices (OVDs)-Twinvisc (OVD 1) and Duovisc (OVD 2)-in cataract surgery. SETTING: European multicenter study. DESIGN: Prospective randomized controlled study. METHODS: Patients with cataract had phacoemulsification and intraocular lens implantation in 1 eye. They were randomly assigned to receive OVD 1 or OVD 2. Preoperative and postoperative examinations over 3 months included mean intraocular pressure (IOP), incidence of IOP peaks (≥30 mm Hg and ≥24 mm Hg), endothelial cell count (ECC), corneal thickness, and intraocular inflammation. A subjective evaluation of the OVDs was performed. RESULTS: The study comprised 220 patients. The incidence of IOP peaks and the mean IOP were not statistically significantly different between the 2 groups at any of the follow-up visits. At 6 hours, the incidence of IOP spikes 30 mm Hg or higher was 6.5% and 7.2% in the OVD 1 and the OVD 2 groups, respectively (P = .846). For the IOP spikes 24 mm Hg or higher, the incidence was 16.8% and 25.2%, respectively (P = .128). Three months postoperatively there was no statistically significant difference in ECC and pachymetry between the 2 groups. Mild inflammation was noticed up to 7 days postoperatively after which it resolved in both groups. Subjectively, the OVD 2 was easier to use, whereas the OVD 1 had better cohesive and dispersive properties. CONCLUSIONS: Both OVDs have similar performance and safety profiles in phacoemulsification cataract surgery. No clinically relevant differences were found between the 2 devices regarding transient IOP spikes, mean IOP, corneal endothelium injury, or inflammation.
Gesehen am 23.08.2018